The Identification of Environmental Parameters which could Influence Soil Bacterial Community Composition on The Antarctic Peninsula - A Statistical Approach - Chong, C.W.; Pearce, D.A.; Convey, P.; Tan, I.K.P. (2012)
We adopted a statistical approach to identify environmental parameters which might be important in structuring the bacterial community in soils on the Antarctic Peninsula. An assessment of soil bacterial community composition at six environmentally distinct locations was made using terminal restriction fragment length polymorphism (T-RFLP) profiling. All locations are near to Rothera Point, on Reptile Ridge and adjacent islands in Ryder Bay, off the west coast of the Antarctic Peninsula, and were selected to maximize the range of environmental variability easily accessible from Rothera Station. A range of environmental variables was determined, and a Spearman rank correlation test was used to link the community structure and environmental variables. We demonstrated that the taxonomic distribution of the soil bacteria among the six study sites was relatively even, especially among the islands within Ryder Bay, although each location possessed a distinct community structure. Significant differences in the environmental conditions and soil chemical parameters allowed us to identify differences in location and soil pH as the environmental variables that could most probably explain the soil bacterial community patterns. This observation is consistent with an increasing number of studies from both Arctic and Antarctic locations, and will contribute to the design of future parameter-specific studies to test the potential functional significance of pH to the Antarctic soil bacterial community.